2022
DOI: 10.1155/2022/3525735
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbial Environment Skews Macrophage Polarization and Contributes to Cervical Cancer Development

Abstract: As a common female reproductive system malignancy, cervical cancer (CC) disturbs numerous women’s health. This study demonstrates the role of the vaginal microbial environment (Peptostreptococcus anaerobius) in cervical cancer. Functional assays, including cell proliferation assay, tube formation assay, and immunofluorescence staining, revealed the effect of Peptostreptococcus anaerobius-treated macrophages on cell proliferation and the angiogenesis process. The tube formation assay disclosed the function of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, researchers also revealed that tumors (CRC, cervical cancer, and endometrial cancer) were associated with the high level of Prevotella genus, which disrupt vagina homeostasis and contribute to bacterial vaginosis 36 , 37 . We also found that the abundance of Peptostreptococcus was significantly increased in EOC patients, which is an opportunistic pathogen and has been proven by Zhou et al ., to promote cervical cancer development via inducing macrophage polarization, which secreted VEGF to benefit the angiogenesis 38 . Although we observed the significant growth in these pathogenic bacteria ( Bacteroides, Prevotella , and Peptostreptococcus ) and the reduction in probiotics ( Bifidobacterium ), the specific mechanism of these bacteria in EOC progression awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers also revealed that tumors (CRC, cervical cancer, and endometrial cancer) were associated with the high level of Prevotella genus, which disrupt vagina homeostasis and contribute to bacterial vaginosis 36 , 37 . We also found that the abundance of Peptostreptococcus was significantly increased in EOC patients, which is an opportunistic pathogen and has been proven by Zhou et al ., to promote cervical cancer development via inducing macrophage polarization, which secreted VEGF to benefit the angiogenesis 38 . Although we observed the significant growth in these pathogenic bacteria ( Bacteroides, Prevotella , and Peptostreptococcus ) and the reduction in probiotics ( Bifidobacterium ), the specific mechanism of these bacteria in EOC progression awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There were several other genera being great importance in disease prediction, such as Streptomyces , Peptostreptococcus , Bauldia , since their coexistence in both models. Genus Peptostreptococcus might benefit the development of cervical cancer 42 . Additionally, when vaginal homeostasis is disrupted, for example, the replacement of Lactobacillus population by other microbes, favors the growth of Peptostreptococcus anaerobius 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Genus Peptostreptococcus might benefit the development of cervical cancer. 42 Additionally, when vaginal homeostasis is disrupted, for example, the replacement of Lactobacillus population by other microbes, favors the growth of Peptostreptococcus anaerobius. 43 While for Streptomyces and Bauldia, there are few information available with regard to vaginal microbiota.…”
Section: Diagnostic Potential Of Hrcd Based On the Vaginal Microbial ...mentioning
confidence: 99%
“…Studies have demonstrated the role of the vaginal microbial environment (anaerobic Actinomyces) in cervical cancer [23]. Functional assays, including cell proliferation, tube formation, and immuno uorescence staining, have revealed mechanisms by which anaerobic Actinomyces-induced macrophages secrete VEGF, stimulating cervical cancer angiogenesis in vitro and in vivo.…”
Section: Initial Investigations Have Revealed a Distinctive Compositi...mentioning
confidence: 99%